Development of swine-specific DNA markers for biosensor-based halal authentication - Md. Eaqub, Ali; Uda, Hashim, Prof. Dr.; Muhammad, Kashif; Shuhaimi, Mustafa, Assoc. Prof Dr.; Yaakob, Che Man, Prof. Dr. (Fundacao de Pesquisas Cientificas de Ribeirao Preto (FUNPEC-RO), 2013)
Link to publisher's homepage at http://www.funpecrp.com.br/